Non‐syndromic autosomal recessive congenital ichthyosis in the Israeli population. (26th April 2013) - Israeli, S.; Goldberg, I.; Fuchs‐Telem, D.; Bergman, R.; Indelman, M.; Bitterman‐Deutsch, O.; Harel, A.; Mashiach, Y.; Sarig, O.; Sprecher, E.
Summary Background Autosomal recessive congenital ichthyosis (ARCI) is the term given to a complex and heterogeneous group of cornification disorders associated with mutations in at least eight distinct genes. Mutation distribution and prevalence rates are instrumental for the design of diagnostic strategies in ARCI but have not yet been systematically explored in the Israeli population. Previous data suggest that the demographic features specific to Middle Eastern populations, such as a high frequency of consanguineous marriages, may have an effect on the molecular epidemiology of genodermatoses. Methods We systematically assessed all families with ARCI presenting at our clinics over a period of 9 years, using a combination of homozygosity mapping, direct sequencing and PCR–restriction fragment length polymorphism assays. Results In total, 20 families with ARCI were assessed, and causative mutations were identified in 7 genes: TGM1 (30% of patients), ALOX12B (20%), ABCA12 (5%), CYP4F22 (10%), ALOXE3 (10%), LIPN (5%) and NIPAL4 (5%) Two families (10%) had mutations mapped to an ARCI‐associated locus on 12p11.2–q13, while no mutation was found for one additional kindred. In the subgroup of families of Arab Muslim origin, mutations were identified most frequently in ALOX12B and TGM1 (31%), whereas the other subgroups displayed a subtype distribution very similar to that previously reported in western populations. Conclusions The present data point to the need for population‐tailored mutation screening strategies in genetically heterogeneous genodermatoses, based on the relative prevalence of the disease subsets.